2022
DOI: 10.3389/fgwh.2022.850796
|View full text |Cite
|
Sign up to set email alerts
|

Exposing Obstetric Violence in the Eastern Mediterranean Region: A Review of Women's Narratives of Disrespect and Abuse in Childbirth

Abstract: BackgroundObstetric violence (OV) threatens the provision of dignified, rights-based, high-quality, and respectful maternal care (RMC). The dearth of evidence on OV in the Eastern Mediterranean Region poses a knowledge gap requiring research to improve rights-based and respectful health practice and policy. While efforts to improve the quality of maternal health have long-existed, women's experiences of childbirth and perceptions of dignity and respect are not adequately or systematically recorded, especially … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 71 publications
(279 reference statements)
0
11
0
Order By: Relevance
“…Still, there is limited information available about the quality of care during the childbirth process in the region. A recent scoping review of the EMR reported that the most common types of mistreatment during childbirth are physical abuse and non-dignified care [ 8 ]. In the past ten years, maternal health indicators have been improving in the occupied Palestinian territory (oPt).…”
Section: Introductionmentioning
confidence: 99%
“…Still, there is limited information available about the quality of care during the childbirth process in the region. A recent scoping review of the EMR reported that the most common types of mistreatment during childbirth are physical abuse and non-dignified care [ 8 ]. In the past ten years, maternal health indicators have been improving in the occupied Palestinian territory (oPt).…”
Section: Introductionmentioning
confidence: 99%
“…This is an example of very disrespectful care and may be occurring, unacknowledged, in many other countries as a recent systematic review [ 39 ] failed to find any research in this area. Not gaining women’s consent for interventions or procedures is not uncommon, as is shown in systematic reviews [ 40 , 41 ] and in studies conducted in a myriad of settings globally [ 15 17 , 41 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…11 The knowledge and awareness level of the participants regarding OV and women rights might be more common to people living to urban due to several exposures. 35,48 In another study conducted at Northern Nigeria, it was reported that lack of awareness on RMC because of lower level of education may contribute to their inability to differentiate between acceptable standard of care, and abusive care. 38 We also found that women whose husbands were employed were protected against any form of OV during labor and childbirth compared to their counterparts.…”
Section: Discussionmentioning
confidence: 99%